Combination of Tangeretin and 5-Fluorouracil Modulates Cell Cycle and Induce Apoptosis on Widr Cells - Indriyani, Luthfia; Hermawan, Adam; Jenie, Riris Istighfari (Indonesian Journal of Cancer Chemoprevention, 2012)
Co-chemotherapeutics approaches are increasing in cancer treatment in order mainly to suppress the resistance phenomenon of cancer treatment and to enhance the cytotoxic effect of the main chemotherapeutics agent. Tangeretin has been known to have cytotoxic effect to some cancer cells through some pathways in the cells. To explore the potential effect of tangeretin as co-chemotherapeutics agent this research was subjected to study the cytotoxic Â effect of tangeretin in combination with 5-Fluoro Uracil (5-FU) on WiDR colon cancer cells covering the modulation of cell cycle and apoptosis induction. Cytotoxic effect was examined by using MTT assay while apoptosis induction was determined by annexin-V flowcytometry. Under MTT assay, tangeretin showed weak cytotoxic activity on the cells. However, tangeretin significantly enhanced the cytotoxic effect of 5-FU on the cells. This co-chemotherapeutics effect likely correlated with cell cycle modulation effect, especially in inducing polyploidy phenomenon as expressed in the flowcytometric graph of the DNA content. This combination also increased apoptosis induction. These result suggest that tangeretin is potential to be developed as co-chemotherapeutic agent for 5-FU on colon cancer and further molecular mechanism need to be exploredKeywords : Tangeretin, 5-Fluorourasil, WiDr, cell cycle, apoptosis